2015
DOI: 10.1371/journal.pone.0132865
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Profile of Nociceptin/Orphanin FQ Receptors Interacting with G-Proteins and β-Arrestins 2

Abstract: Nociceptin/orphanin FQ (N/OFQ) controls several biological functions by selectively activating an opioid like receptor named N/OFQ peptide receptor (NOP). Biased agonism is emerging as an important and therapeutically relevant pharmacological concept in the field of G protein coupled receptors including opioids. To evaluate the relevance of this phenomenon in the NOP receptor, we used a bioluminescence resonance energy transfer technology to measure the interactions of the NOP receptor with either G proteins o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
66
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(77 citation statements)
references
References 61 publications
7
66
3
Order By: Relevance
“…In addition, although the effects of 100 nmol N/OFQ lasted for 2.5 hours (Ko et al, 2006), those elicited by 1 nmol PWT2-N/OFQ were still statistically significant 24 hours after the spinal injection . These recent findings demonstrated that that the PWT can be successfully applied to the peptide sequence of N/OFQ to generate tetrabranched derivatives characterized by a Calo' et al, 2000b), b (Malfacini et al, 2015), c (McDonald et al, 2003b), d ), e (Calo' et al, 2002b, f (Trapella et al, 2006), g (Bigoni et al, 2000), h , i (Fischetti et al, 2009b). Underscored data indicate pA 2 values obtained from Schild plots.…”
Section: A Nociceptin/orphanin Fq Related Peptidesmentioning
confidence: 98%
See 4 more Smart Citations
“…In addition, although the effects of 100 nmol N/OFQ lasted for 2.5 hours (Ko et al, 2006), those elicited by 1 nmol PWT2-N/OFQ were still statistically significant 24 hours after the spinal injection . These recent findings demonstrated that that the PWT can be successfully applied to the peptide sequence of N/OFQ to generate tetrabranched derivatives characterized by a Calo' et al, 2000b), b (Malfacini et al, 2015), c (McDonald et al, 2003b), d ), e (Calo' et al, 2002b, f (Trapella et al, 2006), g (Bigoni et al, 2000), h , i (Fischetti et al, 2009b). Underscored data indicate pA 2 values obtained from Schild plots.…”
Section: A Nociceptin/orphanin Fq Related Peptidesmentioning
confidence: 98%
“…The sodium binding pocket collapses upon receptor activation, thus suggesting that presence of sodium may stabilize the receptor in an inactive conformation . Very recently using a BRET-based assay to investigate NOP receptor/G-protein interactions, it was demonstrated that GDP was not able to significantly inhibit the baseline BRET ratio (Malfacini et al, 2015). However, in membranes expressing the other opioid receptors, under similar experimental conditions, GDP can suppress the baseline BRET ratio, indicating a reduction in spontaneous receptor/G-protein interactions, with maximal effects 4-5 times greater at delta than mu receptors (Vezzi et al, 2013).…”
Section: A Nociceptin Opioid Peptide Receptor Proteinmentioning
confidence: 99%
See 3 more Smart Citations